Perempuan dan Patriarki: Gambaran Diskriminasi Terhadap Perempuan dalam Budaya Bali - Suari Dewi, Ni Made; Ni Made Suari Dewi; Tobing, David Hizkia (Center of Gender Studies and Child of State Islamic Institute of Metro, 2025)
Patriarchy is a system that is still developing in Balinese culture. This system can exist because there is a hereditary belief which states that the person who must continue the family lineage and become the heir is a men. Some research found that there were many injustices received by women which benefited men because men were considered more important. The existence of this system results in various discrimination and injustice against women in areas such as the household, family, education, politics, economics and inheritance rights. This research aims to explore discrimination that Balinese women receive due to the existence of a patriarchal system that is still developing in various aspects of life. This research was carried out using literature review method, by collecting and analyzing data from various articles that relevant to the research topic. The results of this research is, there is four major groups aspects of discrimination received by Balinese women were obtained, including, Marginalization, Subordination, Negative Stereotypes, and Violence. Keywords: balinese women, patriarchy in Bali, discrimination against women, gender inequality